The evaluation of reactive stresses in TiNi shape memory alloys. (4th August 2014) - Filip, Peter; Mazanec, Karel
The reactive stresses of tensile prestrained specimens were investigated in two hot–rolled TiNi alloys. The Alloy A, which contained 50.8 at% Ni, exhibited pseudoelastic properties at room temperature. Alloy B (49.5 at% Ni) had a martensitic structure at room temperature. Some of the alloy B specimens were further cold–rolled with a reduction of 15%. These were then labelled C specimens. The reactive stresses are higher if the change of the shape is accompanied by a stress–induced martensitic transformation (A specimens). The reactive stressed attained with the C specimens were remarkably higher than those attained with the A and B specimens